Analysis of the economic feasibility of using rainwater for vertical residential type buildings in the City of João Pessoa State of Paraíba (Research, Society and Development, 2021)
The objective of this study is to analyze the economic feasibility of implementing a rainwater catchment system to serve non-potable uses in vertical residential buildings in the city of João Pessoa, state of Paraíba, Brazil, and assess the willingness of the city's population to pay a higher price for a property that has this rainwater catchment system. The first hypothesis considers a variation in the number of floors, ranging from 5 to 30. The second hypothesis considers a variation in the reservoir volume. The volumes considered and tested were 15m³, 25m³, 45m³ and 65m³. Thus, 104 scenarios were created. To verify the population's interest in rainwater harvesting systems and the willingness to pay extra for these systems, a survey was carried out via google forms, for about 70 people. Overall, 79.8% of the scenarios have B/C greater than 1. To the 15m³ reservoir, which presented a greater economic attractiveness, 92.31% of the alternative scenarios B/C greater than 1. The 65m³ reservoir has only 65.38% of the B/C values greater than 1. The best performance was achieved for the scenario of 21 floors and 15m³ reservoir, with the B/C of 1.96, NPV of R$24,446.92 and payback period in 9.3 years. The application of the forms revealed that 96.6% of the population is interested in acquiring a property with the development system and that 57.1% are willing to pay up to 2% more than the property's value.